PENGEMBANGAN TES KETERAMPILAN PROSES SAINS DASAR SD/MI - Widayanti, Esti Yuli (Journal Of Islamic Elementary School (JIES), 2016)
The aim of this research is to develop test instrument validly and reliablely for measuring the process skill of fundamental science of SD/MI upper class students. This research is research and development (R&D), that research method is used to result appropriate product and exam effectiveness. To reach thats’ aim, this research was fulfilled by two fases, those are instrument development process fase and psychometric analisys fase. The first fase insist of: identify objective test, specify test content or describe science process skill will be tested, construct instrument lattice include indicators of every skill and questions of each indicators, and make validation to expert judgement. The second fase is psychometric analisys by piloting test. The results of this research are: 1) it was developed the first test instrument by constructing 24 multiple choice questions validly after revising. 2) it was developed the second test instrument that is psychometric analisys by piloting test to get internal reliability and to know discrimination and difficulty grade. The received items are items those have difficulty grade, discriminant index, and answer distribution matching with these criteria. The result of this fase is that there are 10 item received (item number 1, 2, 7, 8, 9, 15, 17, 18, 22, and 23). 13 item was revised (item number 3, 4, 5, 6, 11, 12, 13, 14, 16, 19, 20, 21, 24), and 1 item was not used (item number 10). The reliability was 0.524, that was the medium reliability.